2021
DOI: 10.1111/jonm.13337
|View full text |Cite
|
Sign up to set email alerts
|

Components of the Magnet® model provide structure for the future vision of nurse managers’ work: A qualitative perspective of nurse managers

Abstract: Aim To describe nurse managers’ views of their work in the future. Background Ongoing reformation of health care organisations includes profound changes to nurse managers’ work practices. Method A qualitative approach was applied to elicit views of nurse managers (n = 133) from eight Finnish specialized medical care hospitals through one open‐ended question about their future work in November 2019. The acquired data were subjected to inductive thematic content analysis. Results Four themes were identified in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 28 publications
4
30
0
Order By: Relevance
“…The findings reveal that SQC has a direct effect on OA ( β = 0.252). As such, the findings support the views of Nurmeksela et al (2021): “ultimately the quality of care is […] a crucial factor in the perception of organizations’ attractiveness” (p. 5). Although the direct relationship between SQC and OA has not been examined previously, these findings indicate that SQC is a type of “customer-linked job satisfaction” (Paulin et al , 2006).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The findings reveal that SQC has a direct effect on OA ( β = 0.252). As such, the findings support the views of Nurmeksela et al (2021): “ultimately the quality of care is […] a crucial factor in the perception of organizations’ attractiveness” (p. 5). Although the direct relationship between SQC and OA has not been examined previously, these findings indicate that SQC is a type of “customer-linked job satisfaction” (Paulin et al , 2006).…”
Section: Discussionsupporting
confidence: 79%
“…The findings reveal that SQC has a direct effect on OA (b = 0.252). As such, the findings support the views of Nurmeksela et al (2021): "ultimately the quality of care is [. .…”
Section: Structural Modelsupporting
confidence: 76%
See 1 more Smart Citation
“…In Finland (Kvist et al, 2013) and Italy (Morsiani et al, 2017), it was also found that nursing leadership needs more development to achieve transformational leadership. In our study, nurses' perception of empowerment for change was a key factor in successful evidence implementation, in accordance with other researchers (Cheng et al, 2018;Cummings et al, 2018;Liukka et al, 2018;Nurmeksela et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Transformational leadership was positively associated with providers' positive attitudes towards adoption of EBP in magnet hospitals (Aarons, 2006;Nurmeksela et al, 2021). Our findings show that mainly in Health Agency hospitals, ward managers try to involve the nurses in the changes and rely on natural leaders to implement evidence, but nurses feel they have little power for change.…”
Section: Discussionmentioning
confidence: 79%